Erythrocyte superoxide dismutase as a biomarker of septic acute kidney injury - Costa, Nara Aline [UNESP]; Gut, Ana Lúcia [UNESP]; Azevedo, Paula Schmidt [UNESP]; Tanni, Suzana Erico [UNESP]; Cunha, Natália Baraldi [UNESP]; Magalhães, Eloá Siqueira [UNESP]; Silva, Graziela Biude; Polegato, Bertha Furlan [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; Balbi, André Luís [UNESP]; Ponce, Daniela [UNESP]; et al. (Elsevier, 2016)
Background: Oxidative stress is a key feature of sepsis and could be a common pathophysiological pathway between septic shock and acute kidney injury (AKI) Our objective was to evaluate the erythrocyte superoxide dismutase (SOD1) activity as predictor of AKI in patients with septic shock. Methods: This is a prospective observational study that evaluated 175 consecutive patients over the age of 18 years with septic shock upon intensive care unit (ICU) admission. However, 43 patients were excluded (27 due to AKI at ICU admission). Thus, 132 patients were enrolled in the study. At the time of the patients’ enrollment, demographic information was recorded. Blood samples were taken within the first 24 h of the patient’s admission to determine the erythrocyte SOD1 activity. All patients were followed throughout the ICU stay, and the development of AKI was evaluated. In addition, we also evaluated 17 control subjects. Results: The mean age of patients with septic shock was 63.2 ± 15.7 years, 53 % were male and the median ICU stay was 8 days (4–16). Approximately 50.7 % developed AKI during the ICU stay. The median erythrocyte SOD1 activity was 2.92 (2.19–3.92) U/mg Hb. When compared to control subjects, septic shock patients had a higher serum malondialdehyde concentration and lower erythrocyte SOD1 activity. In univariate analysis, erythrocyte SOD1 activity was lower in patients who developed AKI. The ROC curve analysis revealed that lower erythrocyte SOD1 activity was associated with AKI development (AUC 0.686; CI 95 % 0.595–0.777; p < 0.001) at the cutoff of <3.32 U/mg Hb. In the logistic regression models, SOD1 activity higher than 3.32 U/mg Hb was associated with protection of AKI development when adjusted by hemoglobin, phosphorus and APACHE II score (OR 0.309; CI 95 % 0.137–0.695; p = 0.005) and when adjusted by age, gender, chronic kidney disease, admission category (medical or surgery) and APACHE II score (OR 0.129; CI 95 % 0.033–0.508; p = 0.003). Conclusions: In conclusion, our data suggest that erythrocyte SOD1 activity could play a role as an early marker of septic AKI and could be seen as a new research avenue in the field of biomarker in AKI. However, our study did not show a strong correlation between SOD activity and AKI. Nevertheless, these original data do warrant further research in order to confirm or not this hypothesis.
Keywords: Acute kidney injury; Oxidative stress; Sepsis; Superoxide dismutase